2023
DOI: 10.1021/acsomega.3c05896
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Energy Transfer between Higher Excited States of Photosynthetic Pigments: 2. Chlorophyll b is a B Band Excitation Trap

Jan P. Götze,
Heiko Lokstein

Abstract: Chlorophylls (Chls) are known for fast, subpicosecond internal conversion (IC) from ultraviolet/blue absorbing (“B” or “Soret” states) to the energetically lower, red light-absorbing Q states. Consequently, excitation energy transfer (EET) in photosynthetic pigment–protein complexes involving the B states has so far not been considered. We present, for the first time, a theoretical framework for the existence of B–B EET in tightly coupled Chl aggregates such as photosynthetic pigment–protein complexes. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…This enhances the effective B band depletion by Crts, as it does not matter if a photon is directly absorbed by Crts or if the S 2 excitation is resulting from B → S 2 EET; the result is the same. This aspect will also be explored in the next article in this series …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This enhances the effective B band depletion by Crts, as it does not matter if a photon is directly absorbed by Crts or if the S 2 excitation is resulting from B → S 2 EET; the result is the same. This aspect will also be explored in the next article in this series …”
Section: Resultsmentioning
confidence: 99%
“…It is also shown that a simple and efficient solution to the Chl B–B EET problem is the presence of Crts. Crts efficiently compete for Chl B state excitations, both via initial spectral filtering (discussed in detail in the next article of this series 71 ) and then through a high likelihood of acting as FRET acceptors (in CP29, at least 39% B–B excitation reduction). Due to rapid internal conversion and their strongly shifted emission spectrum, they cannot donate the energy back into the B band.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our article titled “Excitation Energy Transfer between Higher Excited States of Photosynthetic Pigments: 1. Carotenoids Intercept and Remove B Band Excitations” (DOI: ), , we computationally approximated the fluorescence yields of chlorophylls (Chls) and carotenoids (Crts). During the calculations of the theoretical values, an input/output error in the code resulted in reading the absorption spectrum twice instead of reading the emission and absorption spectrum.…”
Section: Amentioning
confidence: 99%